Chimney parallel grafts and thoracic endovascular aortic repair for blunt traumatic thoracic aortic injuries: A systematic review. (April 2019) - Carter, Rebeca; Wee, Ian Jun Yan; Petrie, Kyle; Syn, Nicholas; Choong, Andrew MTL
Background: Whilst the management of blunt traumatic thoracic aortic injury has seen a paradigm shift to an 'endovascular first' approach, the limitations of thoracic endovascular aortic repair remain. An inadequate proximal landing zone limits the use of thoracic aortic stent grafts and in an emergent polytrauma setting, aortic arch debranching via open surgery may not be practical or feasible. A wholly endovascular approach to debranching utilising 'off-the-shelf' stents and parallel graft techniques may represent a possible solution. Hence, we sought to perform a systematic review investigating the use of chimney graft techniques alongside thoracic aortic stenting in blunt traumatic thoracic aortic injury. Methods: We performed the systematic review in accordance to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Searches were performed on Medline (PubMed), Web of Science and Scopus to identify articles describing the use of chimney grafts in traumatic aortic transection (PROSPERO: CRD42017082549). Results: The systematic search revealed 172 papers, of which 88 duplicates were removed resulting in 84 papers to screen. Based on title, abstract and full text review, six articles were included for final analysis. There were nine patients in total with an average age of 41 (three females, five males, one unspecified), all with significant polytrauma, secondary to the mechanism of injury. A variety of stents were used between centres, with techniques showing a predominance to stenting of the left subclavian artery (77%, n  = 7). The technical success rate was 82%, with two (18%) cases of type 1 endoleaks, of which one resolved spontaneously. Conclusions: Despite the encouraging results, this by no means provides for a firm conclusion given the small sample size. Patients should still be judiciously selected on a case-by-case basis when employing the chimney graft technique. Larger cohort studies are needed to establish these findings.